“…Rejected by Everybody All Her Life…” Adverse Childhood Issues in Toni Morrison’s Novel God Help The Child (2015) - Lahtiva Rahmadaniah Putri; Leni Marlina (English Language and Literature, 2023)
The goal of this study is to examine the adverse childhood that the protagonist of Toni Morrison's book "God Help the Child" had to deal with. There is evidence that adverse childhood experiences (ACEs) can cause anxiety and depression. In this case, adolescents are more likely to feel anxiety and depression. This is the result of an adolescent having a mental health issue. . Adversity in adolescents has a significant impact on short and long-term outcomes. Since she was a child, the character has gone through harsh experiences. Felitti's theory of adverse childhood (2018) is relevant to this analysis. This theory is based on how the text has been interpreted and how the novel is being read. Through the use of quotations in the book, information is gathered. Sentences and paragraphs make up the data that was gathered. The results of the study show that the characters who face adverse childhood experiences can be seen through: (1) the main character has different skin colors at birth from his parents so that his parents do not accept him, (2) the main character gets various treatments that lead to the adverse childhood experiences he gets from their environment and parents. Therefore, the various bad treatment received by the main character is the main issue of adverse childhood experiences in the novel.